Assessing Information Landscape in Nepal through Constructive Approach - Aryal, Kundan (Molung Educational Frontier, 2025)
Constructive journalism (CJ) was initiated in Europe with the goal of countering the negativity bias in news. It also resembles the concept of development journalism that emerged in the late 1960s in Asia. CJ aims to empower readers by providing them with information and tools to effect positive change in their lives nearly a decade and a half ago. Thus, CJ is a noble attempt in journalism to instill distinct news values. This article employs the theoretical framework of CJ to evaluate the media landscape in Nepal. Throughout this assessment, several news stories from different Nepali newspapers and online newsportals have been scrutinized according to the three pillars of CJ. The systematic observation reveals that Nepali media largely fall short of adhering to the constructive approach to journalism. Therefore, the state of CJ in the context of Nepal has yet to advance.